Collective memories and previous experiences of older people in the face of disaster risk processes: lessons learned, implication, and social support - Sandoval-Díaz, José; Navarrete-Valladares, Camila; Suazo-Muñoz, Consuelo; Martínez-Labrín, Soledad (Frontiers in Climate, 2023)
Introduction: Climate change amplifies the vulnerability of various groups, especially of older people. Though seen as highly vulnerable, studies reveal their remarkable resilience and that they experience less distress than the young population. Collective memory and experience thus act as coping devices, facilitating learning processes and adaptation when faced with natural risks.The objective was to characterize the lessons learned, implications and social support perceived by the older people in disaster risk situations. The study was conducted with six groups of older people in Ñuble (Chile) using the SWOT matrix (Strengths, Weaknesses, Opportunities, and Threats), life stories, focus groups, photo evocation and other participatory techniques. Content analysis was based on a systematic coding of category quantifications.Results: Negative impacts and positive learning processes were identified that prompted significant changes and made post-traumatic growth processes and capacity-building possible. The type of disaster, its frequency and stage in which it occurs influence the perception of risk and coping strategies, underscoring the importance of strengthening communication about natural risks that are often rendered invisible, such as heat waves.Social support is the main source of collective capacity and has been shown to reduce perceived vulnerability to disaster risk scenarios.The collective memory and prior disaster experiences of the older people provide them with tools to reinterpret new risk scenarios, highlighting their abilities and promoting their empowerment. These resources are crucial for the development of intergenerational learning aimed at comprehensive risk management. However, facing recent disaster risk situations such as Covid-19 or heatwaves has posed a challenge due to a lack of prior experiences and knowledge on how to handle them. This underscores the importance of having continuous psychoeducation, tailored to the specific and territorial needs of the older people, especially in the context of climate change.